2014
DOI: 10.3109/21678421.2014.971813
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences among amyotrophic lateral sclerosis cases in the United States

Abstract: Our objective was to describe racial and ethnic differences of amyotrophic lateral sclerosis (ALS) in distinct geographic locations around the United States (U.S.). ALS cases for the period 2009–2011 were identified using active case surveillance in three states and eight metropolitan areas. Of the 5883 unique ALS cases identified, 74.8% were white, 9.3% were African-American/black, 3.6% were Asian, 12.0% were an unknown race, and 0.3% were marked as some other race. For ethnicity, 77.5% were defined as non-Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
7
45
1
Order By: Relevance
“…The age groups 60-69 years and 70-79 years are the most common ages of diagnosis and those aged 18-39 years are the least. This finding is consistent with reported literature in the United States and abroad (1,6,(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The age groups 60-69 years and 70-79 years are the most common ages of diagnosis and those aged 18-39 years are the least. This finding is consistent with reported literature in the United States and abroad (1,6,(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 93%
“…Incidence rates by race and ethnicity were calculated for all states and metro areas combined and showed that the incidence rate in whites was higher than the incidence rates for blacks and Asians. In addition, the incidence rate in non-Hispanics was significantly higher than the incidence rate in Hispanics (40). Because the states and metro areas were selected to over-represent racial and ethnic minorities, the differences in incidence rates between the individual states and metro areas could be related to the differences in the racial and ethnic make-up of the underlining populations.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Chalabi and Hardiman note that "older patients are more likely to be referred to nonneurological services, and ALS might be under-recognized in older people because being weak or wasted may be regarded as a normal part of ageing, or may be ignored in someone with multiple medical problems" [13]. Consistent with the race-specific mortality rates that we found, other studies have found lower incidence and mortality rates among non-whites [16,17]; however, the majority of population-based epidemiologic studies of ALS have been persons of European ancestry [13]. Similarly, other studies have also found lower ALS mortality rates among Hispanics [1,17].…”
Section: Discussionsupporting
confidence: 81%
“…However, in the present study, the vast majority of the ALS patients in this study were of white Caucasian background. This is in keeping with the higher incidence of ALS in white Caucasian individuals (compared to black, Asian and Hispanic individuals) in large population studies (Cronin et al, 2007, Rechtman et al, 2015. Therefore, applying BAI to an ALS population that predominantly includes white Caucasian individuals, could account for some of the inaccuracy observed between BAI and FM in this study.…”
Section: The Complex Relationship Between Anthropometric Measures and Fmsupporting
confidence: 75%